Festival or Sport? Chinese Motivations to a Modern Urban Hiking Event. (January 2021) - Chen, Fangfang; Naylor, Michael; Li, Yanning; Dai, Shanshan; Ju, Peng
Festive sport events provide an opportunity for people to engage in leisure in an atmosphere of celebration. It has become increasingly popular in China. Although motivations have been explored thoroughly in the context of participant and recreational sport, events, and festivals, no research has yet focused on the overlap among these domains. To address the gap, this study is an investigation of what motivates people to participate in festive sport events as an emerging subcategory of more traditional events and festivals. After the development of a new motives scale, a questionnaire was administered to 894 participants in a festive sport event for hikers in China. The sample was split in three to validate the scale using factor analysis. Six participant motives in the context of a festive sport event emerged including Physical Health, Achievement, Socialization, Mental Health, Novelty/Excitement, and Culture/Event. Important implications of this study are also discussed.